ICT-ENHANCED MARITIME ENGLISH TEACHING AND LEARNING AT TERTIARY LEVEL. A CONTRASTIVE ANALYSIS - BOERU, Mariana (Studia Universitatis Babeș-Bolyai Philologia, 2024)
ICT-Enhanced Maritime English Teaching and Learning at Tertiary Level. A Contrastive Analysis. This article aims to investigate the academic impact of employing ICT means and approaches in the context of teaching ESP to Marine Electrical Engineering students at “Mircea cel Batran” Naval Academy, Romania. The research question to be answered is whether a switch from a face-to-face, paper-based learning setting to a face-to-face, digital, interactive one would influence the overall academic performance of our students, with a focus on elements such as student interest, motivation, and autonomy. The article reports on and discusses the findings of quantitative and qualitative research conducted by the author on two separate groups of second-year Naval Academy students. First, a control group was selected and offered the traditional, paper-based, face-to-face course in English for Marine Electrical Engineering for the second year of study, while the experiment group was exposed to the digital, interactive version of the same course, which had been uploaded on the Academy Moodle LMS platform. Both groups underwent identical mid-semester and final semester assessments, and their results were recorded and compared. A keen interest was taken in the exposed levels of specialized lexical content retention and its subsequent, successful communicative contextualization. Moreover, the research cohorts were administered an end-of-semester questionnaire that sought to identify how students related to the course materials in terms of their level of interest and motivation and the perceived relevance and efficiency of the course content and format, etc. In addition to the contrastive evaluation of the course methodology employed in both cases under investigation, the research study also looked at the students’ perceptions of the added value of several other factors, such as access to course materials and the possibility and ease of self-study, which correlate with the development of students’ learning autonomy and the acquisition of transversal skills for life-long learning. Ultimately, this article seeks to bring into discussion some key aspects of integrating ICT means into the teaching of ESP at the tertiary level, as technology-informed ESP has become an indisputable and inevitable evolution within 21st century language teaching practices. REZUMAT. Predarea și învățarea limbii engleze maritime prin intermediul mijloacelor TIC la nivel universitar. O analiză contrastivă. Acest articol își propune să investigheze impactul academic al utilizării mijloacelor TIC în contextul predării limbii engleze de specialitate pentru studenții la Inginerie Electrică și Electronică Navală, din cadrul Academiei Navale „Mircea cel Bătrân”, România. Întrebarea de cercetare a acestui studiu este dacă trecerea de la un context de învățare față în față tradițional, la unul față în față digital, interactiv, ar influența performanța academică generală a studenților noștri. Cercetarea vizează acele elemente precum interesul studenților, motivația și autonomia lor de învățare. Articolul raportează și analizează rezultatele cercetărilor cantitative și calitative efectuate de autor pe două grupuri separate de studenți din anul II la Academia Navală. În primul rând, a fost selectat un grup de control care a urmat cursul de limba engleză pentru inginerie electrică marină, anul II de studiu, în format tradițional față în față, în timp ce grupul experimental a fost expus la versiunea digitală, interactivă a aceluiași curs, care fusese încărcat pe platforma online Moodle a Academiei Navale. Ambele grupuri au fost supuse unor evaluări identice la jumătatea semestrului și la final de semestru, iar rezultatele lor au fost înregistrate și comparate. Un interes deosebit a fost acordat gradului de retenție a conținutului lexical specializat și contextualizarea comunicativă ulterioară a acestuia. Mai mult, studenților vizați de studiu li sa administrat un chestionar de sfârșit de semestru care a urmărit să identifice modul în care aceștia se raportează la materialele de curs în ceea ce privește nivelul lor de interes și motivație și relevanța și eficiența percepută a conținutului și formatului cursului etc. Pe lângă evaluarea contrastivă a metodologiei de curs folosită în ambele cazuri investigate, studiul de cercetare a analizat și percepțiile studenților cu privire la valoarea adăugată a mai multor alți factori, cum ar fi accesul la materialele de curs și posibilitatea și ușurința studiului individual, care se corelează cu dezvoltarea autonomiei de învățare și dobândirea de competențe transversale pentru învățarea pe tot parcursul vieții. În esență, acest articol urmărește să aducă în discuție câteva aspecte cheie ale integrării mijloacelor TIC în predarea limbii engleze de specialitate la nivel academic, deoarece predarea limbajelor de specialitate bazată pe tehnologie a devenit o evoluție incontestabilă și inevitabilă în cadrul practicilor de predare a limbilor străine din secolul XXI. Cuvinte-cheie: predarea limbajelor de specialitate, mijloace TIC, e-learning, digitalizare, cercetare contrastivă Article history: Received 6 March 2024; Revised 25 June 2024; Accepted 15 October 2024; Available online 10 December 2024; Available print 30 December 2024.